2013
DOI: 10.1051/0004-6361/201321533
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-dependent UV photodesorption of pure N2and O2ices

Abstract: Context. Ultraviolet photodesorption of molecules from icy interstellar grains can explain observations of cold gas in regions where thermal desorption is negligible. This non-thermal desorption mechanism should be especially important where UV fluxes are high. Aims. N 2 and O 2 are expected to play key roles in astrochemical reaction networks, both in the solid state and in the gas phase. Measurements of the wavelength-dependent photodesorption rates of these two infrared-inactive molecules provide astronomic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(137 citation statements)
references
References 61 publications
(106 reference statements)
10
125
2
Order By: Relevance
“…This indicates that photodesorption of some ice species like CO and N 2 is mainly driven by a desorption induced by electronic transition (DIET) process (Fayolle et al 2011(Fayolle et al , 2013. The lowest photodesorption reported by Fayolle et al (2011) at the Ly-α wavelength (121.6 nm) is <6 × 10 −3 molecules per incident photon, coinciding with the low VUV-absorption at this wavelength in Fig.…”
Section: Speciesmentioning
confidence: 66%
See 1 more Smart Citation
“…This indicates that photodesorption of some ice species like CO and N 2 is mainly driven by a desorption induced by electronic transition (DIET) process (Fayolle et al 2011(Fayolle et al , 2013. The lowest photodesorption reported by Fayolle et al (2011) at the Ly-α wavelength (121.6 nm) is <6 × 10 −3 molecules per incident photon, coinciding with the low VUV-absorption at this wavelength in Fig.…”
Section: Speciesmentioning
confidence: 66%
“…The performance of VUV-spectroscopy inevitably leads to exposure of the sample to irradiation, often causing photodestruction or photodesorption of the ice molecules to some extent during spectral acquisition (e.g., d 'Hendecourt et al 1985'Hendecourt et al , 1986Bernstein et al 1995;Gerakines et al 1995Gerakines et al , 1996Schutte 1996;Sandford 1996;Muñoz Caro et al 2003Dartois 2009;Öberg et al 2009a,b;Fillion et al 2012;Fayolle et al 2011Fayolle et al , 2013, and references therein). Photoproduction of new compounds and the decrease of the starting ice column density was monitored by IR spectroscopy.…”
Section: Vuv-absorption Cross Section Of Interstellar Polar Ice Analogsmentioning
confidence: 99%
“…We do not allow H 2 isotopologues to stick to grains because for H 2 this requires temperatures of < ∼ 4 K. A UV photodesorption yield of 3 × 10 −3 was adopted (e.g., Öberg et al 2009a,b;Fayolle et al 2011aFayolle et al , 2013. Photodissociation processes of solid species are taken from Garrod & Herbst (2006) and Semenov & Wiebe (2011).…”
Section: Chemical Modelmentioning
confidence: 99%
“…Photodesorption rates for several molecules using synchrotron radiation (Fayolle et al 2011(Fayolle et al , 2013 as well as direct cross section measurements of the main constituents of interstellar ice show strong wavelength dependences in the VUV domain. (Cruz-Diaz et al 2014a,b) Recently, Chen et al (2014) showed that the differences in CO photodesorption rates reported by various groups over the past decade may be partly explained by differences in MDHL emission spectra.…”
Section: Introductionmentioning
confidence: 99%